Disorders of Adipose Tissue and Lipodystrophies: Causes, Consequences, and Treatment Perspectives - Rosińska Kamila Rosińska; Ewelina Justyna Janicka; Julia Natalia Skibicka; Monika Niedźwiedzka; Mateusz Rosiński (Quality in Sport)
Lipodystrophies are rare metabolic disorders characterized by the loss of adipose tissue, which can manifest as generalized, partial, or localized. This condition is associated with metabolic complications such as insulin resistance, diabetes, hypertriglyceridemia, and liver steatosis. The paper discusses the classification of lipodystrophies by etiology and fat loss extent, including generalized and partial forms, both congenital and acquired. Special focus is placed on HIV-associated lipodystrophy due to the prevalence of antiretroviral therapy. The pathophysiology involves disrupted adipogenesis, leading to abnormal fat distribution and metabolic dysfunction. Diagnosis includes medical history, physical exams, and body composition analysis. Treatment focuses on managing metabolic issues and may involve therapies like metreleptin.